COMMUNITY STRUCTURE OF WATERBIRDS IN SEVERAL TYPE OF WETLAND UTILIZATION IN EAST COAST OF SURABAYA - Ragil Siti Rihadini; Thin Soedarti; Bambang Irawan (The East Java Biological Society, 2012)
Natural wetlands are the natural habitat of waterbirds, but it is very diffi cult to fi nd an unspoiled wetlands without human interventioncurently. East coast of Surabaya is wetlands area in Surabaya that most of the region have change into fi shpond and residental. Theaims of this reasearch are to determine the community structure of waterbirds in each type of wetland utilization and to determine ifthe different type of wetland utilization infl uence the community structure of waterbirds in East Coast of Surabaya. Data were collectedduring August 2012 to January 2013 with point count method. Six sampling plots have been selected. Six sampling plots representingfour types of use of wetlands, which are bozem, the former fi shpond, fi shpond with vegetation, and fi shponds without vegetation (fi shpond1, fi shpond 2 and fi shpond 3). In bozem recorded 19 species of waterbirds (1107 individual), dominated by shorebirds, with a diversityindex (H') 1.86, and evenness index (J') 0.63. In former fi shpond recorded 7 species of water birds (168 individual), dominated by railsand moorhen, with H’ = 1.12 and J’ = 0.57. In fi shpond with vegetation recorded 12 species of water birds (137 individual), dominatedby large wader, with H’ = 1.85 and J’ = 0.74. In fi shpond 1 recorded 18 species of water birds (299 individual), dominated by terns,with H’ = 1.96 and J’ = 0.68. In fi shpond 2 recorded 9 species of water birds (70 individual), dominated by terns, with H’ = 1.73 andJ’ = 0.79. In fi shpond 3 recorded 10 species of water birds (83 individual), dominated by terns, with H’ = 1.84 and J’ = 0.80. Chi-squaretest showed that X2 count is greater than X2 table with α < 0.05, which indicates that there is a signifi cant difference of the numberof individuals of each species and the number of individual of each water birds’ group for each type of use of wetlands, so it can beconcluded that different types of use of wetlands affect water bird community structure in the East Coast Surabaya.